2014
DOI: 10.1093/arclin/acu014
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Characteristics of the Postconcussion Symptom Inventory in Children and Adolescents

Abstract: Psychometric characteristics of the Postconcussion Symptom Inventory (PCSI) were examined in both concussed (n = 633) and uninjured (n = 1,273) 5 to 18 year olds. Parent- and self-report forms were created with developmentally appropriate wording and content. Factor analyses identified physical, cognitive, emotional, and sleep factors; that did not load strongly or discriminate between groups were eliminated. Internal consistency was strong for the total scales (α = 0.8-0.9). Test-retest reliability for the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
314
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(324 citation statements)
references
References 26 publications
8
314
1
1
Order By: Relevance
“…Our findings are similar to those of Sady et al 11 in older youths but less than those in younger children (24%). Although we noted similar percentages of headaches across the sexes, results from a recent metaanalysis 17 suggest that females (ages 12À26 years) were more likely than males to report baseline symptoms of headache.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings are similar to those of Sady et al 11 in older youths but less than those in younger children (24%). Although we noted similar percentages of headaches across the sexes, results from a recent metaanalysis 17 suggest that females (ages 12À26 years) were more likely than males to report baseline symptoms of headache.…”
Section: Discussionsupporting
confidence: 90%
“…Approximately 20% of our older group rated fatigue as a moderate problem (ie, score of at least 3 on the PCSI). Results from another large cohort study 11 of children and youth at baseline indicated that fatigue was also the most often reported symptom, albeit to a lesser extent (younger children ¼ 45% and older youth ¼ 35%). We speculate that this may reflect the unique characteristics of our sample: namely elite athletes, who, especially at older ages, spent 3 to 7 days per week participating in their sport in addition to fulfilling academic demands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Participants within each recovery group were further stratified based on level of schooling (grades K through 5 for elementary school, 6 through 8 for middle school, and 9 through 12 for high school) to examine hypothesized grade level differences. Study hypotheses were examined by using x 2 statistics to examine group differences in the type and frequency of academic problems, trouble with classes, levels of concern, and grade status/ change.…”
Section: Methodsmentioning
confidence: 99%